Migration and Sustainable Development: a critical approach - Talamo, Giuseppina (European Journal of Sustainable Development, 2016)
The aim of this paper is to examine international migration studies following an interdisciplinary approach. The starting point is an examination of the increasing international migratory flows, that represents one of the most visible manifestation of the globalization process. Although the recent global crisis has added new concerns in relation to migrant situation particularly in the countries more affected by the recession, analyses of the impact of globalization indicate that migration provides a driving force for sustainable development.. Using recent data, the main characteristics of migration flows in Italy and in Oecd area will be presented. Analyses show that there is a positive correlation between migration and sustainable development, which has often been underestimated or misunderstood. Key Words: Migration, Sustainable Development, Integration.